Management of Ovarian Cancer in the Second Trimester of Pregnancy: A Case Report and Literature Review - Syarief, Sri Dewi Rahmawati; Ritonga, Mulyanusa Amarullah; Anwar, Ruswana; Suardi, Dodi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Introduction: Ovarian carcinoma during pregnancy is a rare but clinically significant condition that requires swift and precise management to optimize maternal and fetal outcomes. This case report highlights the successful conservative surgical management of malignant mucinous ovarian cancer diagnosed in the second trimester. It provides insights into the feasibility and safety of surgical intervention during pregnancy, contributing valuable evidence to the existing literature on oncologic care during pregnancy.Case Illustration: A 21-year-old woman, G1P0A0, presented at 17-18 weeks of gestation with no complaints related to her pregnancy but reported abdominal enlargement over the past three months. At 6 weeks gestation, the patient was diagnosed with an ovarian cyst, later confirmed as a large cystic mass on the right ovary with papillary components through ultrasound. The IOTA simple rules indicate that the mass was suspected to be malignant. The provisional diagnosis was suspected ovarian malignancy with a differential diagnosis of multilocular ovarian cyst. The patient underwent a planned right oophorectomy at 18 weeks gestation. Histopathology revealed a mucinous malignant tumor of the right ovary that had not invaded the right fallopian tube. The pregnancy was continued, and the patient was closely monitored, with plans for further evaluation postpartum.Conclusion: This case highlights the feasibility and safety of conservative surgical management of ovarian cancer in the second trimester, demonstrating that timely intervention can optimize both maternal and fetal outcomes. The successful continuation of pregnancy after surgery reinforces the importance of individualized, multidisciplinary approaches to oncologic care during pregnancy.Penatalaksanaan Kanker Ovarium pada Kehamilan Trimester Kedua: Sebuah Laporan Kasus dan Tinjauan PustakaAbstrakPendahuluan: Karsinoma ovarium pada kehamilan merupakan kondisi yang jarang terjadi tetapi, memiliki implikasi klinis yang signifikan. Penatalaksanaannya memerlukan keputusan yang cepat dan tepat untuk mengoptimalkan hasil bagi ibu dan janin. Laporan kasus ini menyoroti keberhasilan manajemen bedah konservatif pada kanker ovarium mucinous ganas yang terdiagnosis pada trimester kedua kehamilan. Kasus ini memberikan wawasan mengenai kelayakan dan keamanan tindakan bedah selama kehamilan, serta berkontribusi terhadap literatur ilmiah terkait onkologi kehamilan.Ilustrasi Kasus: Seorang wanita berusia 21 tahun, G1P0A0, datang pada usia kehamilan 17 – 18 minggu tanpa keluhan, namun melaporkan pembesaran perut selama tiga bulan terakhir. Pada usia kehamilan 6 minggu, pasien didiagnosis dengan kista ovarium yang kemudian dikonfirmasi sebagai massa kistik besar pada ovarium kanan dengan komponen papiler melalui pemeriksaan ultrasonografi. Berdasarkan IOTA simple rules, massa tersebut dicurigai ganas. Diagnosis sementara adalah dugaan keganasan ovarium dengan diagnosis banding kista ovarium multilokular. Pasien menjalani operasi ooforektomi kanan yang terencana pada usia kehamilan 18 minggu. Hasil histopatologi menunjukkan tumor mukinosa ganas pada ovarium kanan yang tidak menyerang tuba falopi kanan. Kehamilan dilanjutkan, dan pasien dipantau secara ketat dengan rencana evaluasi lebih lanjut setelah persalinan.Kesimpulan: Kasus ini menyoroti kelayakan dan keamanan manajemen bedah konservatif pada kanker ovarium trimester kedua. Intervensi yang tepat dapat mengoptimalkan hasil bagi ibu dan janin. Keberhasilan kelanjutan kehamilan setelah tindakan bedah ini menegaskan pentingnya pendekatan multidisiplin yang disesuaikan dengan kondisi pasien dalam penatalaksanaan kanker pada kehamilan.Kata kunci: kanker ovarium, kehamilan, kanker ovarium musinosum